Brown bear behaviour in human-modified landscapes: the case of the endangered Cantabrian population, NW Spain - Cabral, Pedro Miguel Matos (2019)
Large carnivore populations are recovering in Europe after centuries of population decline. The Cantabrian brown bear Ursus arctos population is endangered, and it is a good example of a large carnivore inhabiting a human-modified landscape. In order to study the impact of human landscape elements on bear behaviour we analysed 10 years of Cantabrian brown bear records. Human activity and structures do not appear to have an impact on the duration or appearance of vigilance behaviour. While bears avoid direct contact with humans, the mere presence of human infrastructure and activities don't not appear to impact its vigilance behaviours. The brown bear seems to be adapted to human coexistence and this should give a different perspective in future conservation efforts; Comportamento do Urso-Pardo em paisagens modificadas pelo Homem: o caso da população Cantábrica em perigo, NO Espanha Resumo: As populações de grandes carnívoros estão a recuperar por toda a Europa após séculos de declínio populacional. A população Cantábrica de urso pardo Ursus arctos encontra-se em perigo e é um bom exemplo de um grande carnívoro que habita uma paisagem modificada pelo Homem. A fim de estudar o impacto dos elementos da paisagem humanizada no comportamento do urso pardo, analisamos 10 anos de registos de comportamento de urso pardo Cantábrico. A atividade e estruturas humanas não parecem ter impacto na duração ou no aparecimento do comportamento de vigilância. O urso-pardo evita o contato direto com os seres humanos, no entanto a mera presença de infraestruturas e atividades humanas não parece ter impacto no comportamento de vigilância. O urso-pardo parece estar adaptado à coexistência humana e isso deverá dar uma perspetiva diferente a futuros esforços de conservação.